FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN BRANDING SEKOLAH DALAM MENINGKATKAN MINAT PENDAFTARAN SISWA (STUDI KASUS DI SMA NEGERI 6 KOTA JAMBI - Padliyan, Reka; Pratiwi, Ngisti; Fitri, Vidia; Rifki, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2024)
This study analyzes the impact of branding strategies on student enrollment interest at SMA Negeri 6 Kota Jambi. Using a qualitative approach, data were collected through interviews, observations, and document studies from the school principal, vice principals, and students. The results show that the school's branding as a